Fostering Mathematical Creativity Through Multiple Solution Tasks - Tyagi , Tarun Kumar (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Fuchs &Gross in 2009, stated that mathematics is one of the primary competencies in everyday life and ranges from simple tasks from counting to simple calculations, forming the bases and foundation of the nation. Over the last decades the needs of the society have changed, and hence the demand for skilled and educated youth possessing 21st-century skills i.e. the 4C‘s (Creativity, Collaboration, Critical Thinking, Communication) has also mushroomed over the past decade. To overpower such, our education system is experiencing a paradigm shift in the method of teaching and learning pedagogies especially with a core like mathematics which forms the bases of conceptualizing and understanding the application and mechanism of world principles and theories. Therefore, core topics such as mensuration, number system, geometry, data handling, and algebra have become the components of learning and priority at earlier stages of childhood. And hence, different and distinguishable pedagogies of the same is explored as one of the most vivid topics in the present community of mathematics education. In 2002, Owen & Fuchs have claimed that visual representations of mathematical concepts result in better gains under certain conditions, hence giving a better opportunity to students with learning abstract and abstruse concepts of mathematics. This paper aims to explore different pedagogies of mathematics teaching and learning through the use of visualizing aids i.e. manipulatives to form a concrete relation with abstraction in mathematics to a physical or real-life association. Over the period of time strategies developed like STAR (Stimulate- Translate—Apply—Relate), IDDEA(Identify—Discuss—Demonstrate—Emphasise—Assess),  VC2(Visualize—Compare—Correlate), aims to break the steps of teaching into a framework, allowing teachers/educator to use and apply different approaches of teaching i.e. visualization of topic through suitable manipulatives effectively. Allowing the teacher to inculcate the 21st-century skills in their learners.